College law for business - ASHCROFT, John D (South-Western Pub)
This text offers a practical approach to law that emphasizes current and relevant topics students need for business transactions. The basic business law concepts are covered without extensive theory, thus making the law more approachable. The substantial breadth of this text, laden with examples and cases, provides an effective introduction to a variety of legal topics.